2021
DOI: 10.21037/apm-21-860
|View full text |Cite
|
Sign up to set email alerts
|

A patient with metastatic non-small cell lung cancer who received pembrolizumab monotherapy after stereotactic body radiotherapy had progression-free survival of nearly 5 years: a case report

Abstract: Lung cancer is a malignancy with the highest morbidity and mortality in the world.Radiotherapy, chemotherapy, targeted therapy, and immunotherapy have been widely used to treat metastatic non-small cell lung cancer (NSCLC). Stereotactic body radiotherapy (SBRT), also known as stereotactic ablation radiotherapy (SABR), can precisely deliver a high dose of radiation to a target in a limited area.SBRT has been established as the standard treatment for patients with early NSCLC who are unsuitable for operation or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In the literature, cases with an overall survival (OS) exceeding 36 months are rare. A Chinese case report from 2021 [31] described a 78-year-old male patient with a history of prolonged tobacco abuse (20 cigarettes per day) and tuberculosis, diagnosed with NSCLC Stage T1N0M0, who underwent surgery and radiation therapy. After one year of radiation treatment, the patient developed lung, liver, cardiac, and bone metastases.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, cases with an overall survival (OS) exceeding 36 months are rare. A Chinese case report from 2021 [31] described a 78-year-old male patient with a history of prolonged tobacco abuse (20 cigarettes per day) and tuberculosis, diagnosed with NSCLC Stage T1N0M0, who underwent surgery and radiation therapy. After one year of radiation treatment, the patient developed lung, liver, cardiac, and bone metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria were ( 1 ) single-arm studies, ( 2 ) reviews/comments/letters, ( 3 ) meeting abstracts, ( 4 ) IT plus SBRT versus SBRT studies, ( 5 ) study protocols, ( 6 ) case reports, and ( 7 ) retrospective studies. Any disagreements were resolved by discussion.…”
Section: Methodsmentioning
confidence: 99%
“…In another phase 1 trial reported by Ye, the ORR was 39% and the median PFS was six months when advanced lung cancer patients were treated with IT plus SBRT ( 6 ). Moreover, several case studies indicated that some advanced patients achieved long-term survival after IT and SBRT ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…On a side note, the duration of immunotherapy after SBRT is also an area with a paucity of research. A Chinese case study reported on a patient with 5 years of PFS following 52 months of extended pembrolizumab monotherapy after SBRT, representing the most prolonged medication duration with the best efficacy among Chinese patients in the literature ( 104 ), suggesting that the duration of ICI treatment may influence survival. The advent of precision medicine for NSCLC means translational research will now have a more important role to play in clinical trials than ever before.…”
Section: Practical Issues To Be Addressedmentioning
confidence: 99%